Effect of mean heart rate on 30-day mortality in ischemic stroke with atrial fibrillation: Data from the MIMIC-IV database - Yao, Shao-li; Chen, Xi-wen; Liu, Jie; Chen, Xiao-rong; Zhou, Yao (Frontiers in Neurology, 2022)
Background: The relationship of mean heart rate(MHR) with 30-day mortality in ischemic stroke patients with atrial fibrillation in the intensive care unit(ICU) remains unknown. This study aimed to investigate the association between MHR within 24 hours of admission to the ICU and 30-day mortality among patients with atrial fibrillation and ischemic stroke. Methods: This retrospective cohort study used data on US adults from the Medical Information Mart for Intensive Care-IV (MIMIC-IV version 1.0) database. Patients with ischemic stroke who had atrial fibrillation for and first time in ICU admission were identified from the MIMIC-IV database. We used multivariable Cox regression models, a restricted cubic spline model, and a two-piecewise cox regression model to show the eﬀect of the MHR within 24 h of ICU admission on 30-day mortality. Results: A total of 1403 patients with ischemic stroke and atrial fibrillation(mean[SD] age, 75.9 [11.4] years; mean[SD]mean heart rate, 83.8[16.1] bpm; 743 [53.0%] female) were included. A total of 212 (15.1%) patients died within 30 days after ICU admission. When MHR was assessed in tertials according to the 25th and 50th percentiles, the risk of 30-day mortality was higher in participants in group 1(<72 bpm; adjusted hazard ratio, 1.23; 95% CI, 0.79~1.91) and group 3(>=82 bpm; adjusted hazard ratio, 1.77; 95% CI, 1.23~2.57) compared with those in group 2 (72 to 82 bpm). Consistently in the threshold analysis, for every 1 bpm increase in MHR, there was a 2.4% increase in 30-day mortality (adjusted HR, 1.024; 95% CI, 1.01-1.039) in those with MHR above 80 bpm patients. Based on these results, there was a J-shaped association between MHR and 30-day mortality in ischemic stroke patients with atrial fibrillation admitted to the ICU, with an inflection point at 80 bpm of MHR. Conclusions : In this retrospective cohort study, MHR within 24 hours of admission was associated with 30-day mortality (nonlinear, J-shaped association) in patients with ischemic stroke and atrial fibrillation in the ICU, with the lowest hazard on the MHR of 80 bpm. This association may provide a theoretical basis for formulating the target strategy of heart rate therapy for these patients.